Aerodynamics Performance of Barn Swallow Bird at Top Speed : A Simulation Study / M.R.M. Nawi and M.S.A. Azhar - Nawi, M.R.M; Azhar, M.S.A (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper presents a simulation study of aerodynamics performance of Barn Swallow bird (Hirundo Rustica) during gliding at top speed. Barn Swallow is generally known as a bird in which can make abrupt changes of direction during flying even at top speed. This is because it has long narrow wings and a forked tail. It could inspire engineers and scientists for the development of small flying machine such as micro-air-vehicle (MAV). Therefore, investigations on its aerodynamics is worthwhile to be carried out. The simulation work has been performed using a commercial computational fluid dynamics (CFD) software, i.e. Ansys Fluent version 15.0 and CATIA as the modelling software. According to previous studies, the fastest that the Barn Swallow can fly is about 13 m/s which is equivalent to Re=48000, thus becomes the constant speed during the simulation. From the simulation, the results of lift and drag coefficients were compared with the experimental data from past study. It is found that the simulation results are in fairly good agreement with the experimental data by showing the same trends and profiles. The significant differences between simulation and experiment is believed mainly due to the effects of feathers attached to the bird's body and wings which could reduce the skin friction significantly. The significant findings of CFD work, which are the illustrations of the pressure contour and velocity vector around the bird's body and wings. The contours could provide the approximate values of pressure and velocities around the bird's body and wings and it is found obeys the Bernoulli's principle.